The Essence of Rights: An Unreliable Boundary?. Issue 6 (September 2019) - Tridimas, Takis; Gentile, Giulia
Abstract: Article 52(1) of the EU Charter of Fundamental Rights lays down respect for the essence of right as one of the requirements that limitations on rights must respect. This provision is not innovative, as it formalizes into EU law the distinction between "core" and "periphery" of rights present in many national constitutions and in the ECJ and ECtHR case law. Nonetheless, the express reference to essence has given unprecedented resonance to that concept. Essence as the "limit of limits" has a Janus-like character. On the one hand, it pronounces that every fundamental right bears a minimum content which is ringfenced from interference by public and private actors. On the other hand, it stresses the malleability of rights and their social function. The core/periphery dichotomy reflects a balancing act moored in European legal tradition whose symbolism outperforms its utility as a judicial tool. This Article examines the essence clause of the Charter in light of the ECJ case law and the constitutional traditions of the Member States and assesses its role in the framework of fundamental rights protection in EU law. The Article first attempts a classification of rights limitations clauses in national constitutions, following which it discusses the interpretation of essence by the Spanish and the Italian Constitutional Courts. The Article then engages with a theoretical discussion of the concept of essence and examines the case law of the ECJ. Lastly, it looks at the limitations of the concept as a rights protection instrument in EU law.